2021
DOI: 10.1021/acs.orglett.1c02598
|View full text |Cite
|
Sign up to set email alerts
|

Annulation of CF3–Imidoyl Sulfoxonium Ylides with 1,3-Dicarbonyl Compounds: Access to 1,2,3-Trisubstituted 5-Trifluoromethylpyrroles

Abstract: A lithium-bromide-promoted nucleophilic substitution/ annulation cascade reaction between CF 3 -imidoyl sulfoxonium ylides and 1,3-dicarbonyl compounds has been established, and the corresponding 1,2,3-trisubstituted 5-trifluoromethylpyrroles have been obtained in 27−78% yield. This reaction features a broad substrate scope and generates dimethyl sulfoxide and H 2 O as byproducts. * sı Supporting InformationThe Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acs.orglett.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Recently, Wu documented a base-promoted [3 + 3] annulation of acyl sulfoxonium ylides with cyclopropenones to give 2-pyrones . In our ongoing interest in sulfoxonium ylide chemistry, we questioned whether it is possible to construct new C–C bonds via nucleophilic substitution of carbanions to sulfoxonium ylides without the participation of a transition metal . Recently, we documented that electron-deficient sulfoxonium ylides are more prone to be attacked by nucleophiles than the electron-rich ones .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wu documented a base-promoted [3 + 3] annulation of acyl sulfoxonium ylides with cyclopropenones to give 2-pyrones . In our ongoing interest in sulfoxonium ylide chemistry, we questioned whether it is possible to construct new C–C bonds via nucleophilic substitution of carbanions to sulfoxonium ylides without the participation of a transition metal . Recently, we documented that electron-deficient sulfoxonium ylides are more prone to be attacked by nucleophiles than the electron-rich ones .…”
Section: Introductionmentioning
confidence: 99%
“…Our design boils down to development of new coupling reagents that are both bulky and reactive. To reconcile these seemingly contradictive criteria, we employed a bifunctional carbene reagent such as CF3-imidoyl sulfoxonium ylides (TFISYs) [57][58][59][60][61][62][63][64][65] bearing a proximal nucleophilic imine nitrogen as well as a bulkyl N-aryl group (Scheme 1c). Consequently, a secondary amide bearing an electrophilic directing group [66][67][68][69][70][71] was applied as the C-H substrate.…”
Section: Chiral Ligands Have Also Been Demonstratedmentioning
confidence: 99%
“…23 Other multiply substituted -CF3-pyrroles have recently been prepared using several different trifluoromethylated building blocks, namely 5-azido- 33 or 5-bromo-4-alkoxy(or amino)-1,1,1trifluoro-pent-3-en-2-ones, 34 CF3-imidoyl sulfoxonium ylides. 35 and 1-(3,3,3-trifluoro-2,2-dihydroxypropyl)pyridin-1-ium bromide. 36 In conclusion, we have found that various 2-R-4-(trifluoromethyl)quinolines bearing an additional nitro group at ring position 6, 7 or 8 can be prepared from 1-CF3-prop-2-yne 1iminium triflates and mononitroanilines in good to high yields.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…32 Anyway, the reaction course is different from our recently published, triphenylphosphane promoted synthesis of -trifluoromethylpyrroles from propyniminium salts 1, which proceeds via 3-dimethylamino-3-trifluoromethylallenyl phosphonium salts. 23 Other multiply substituted -trifluoromethylpyrroles have recently been prepared using several different trifluoromethylated building blocks, namely 5-azido- 33 or 5-bromo-4-alkoxy(or amino)-1,1,1-trifluoro-pent-3-en-2ones, 34 trifluoromethylimidoyl sulfoxonium ylides, 35 and 1-(3,3,3-trifluoro-2,2-dihydroxypropyl)pyridin-1-ium bromide. 36 In conclusion, we have found that various 2-R-4-(trifluoromethyl)quinolines, bearing an additional nitro group at ring position 6, 7 or 8, can be prepared from 1-trifluoromethylprop-2-yne 1-iminium triflates and mononitroanilines in good to high yields.…”
Section: Paper Synthesismentioning
confidence: 99%